Fuentes de agua en el rendimiento de Lactuca sativa L. bajo sistema hidropónico en Santiago de Chuco-La Libertad - Miñano Corro, Joel Abimael (2019)
The present research work was carried out in the district of Santiago de Chuco, region La Libertad, aiming to determining the water sources in the performance of Lactuca sativa L. Var. Capitata cv. White Boston, the variables to be evaluated were fresh weinght. The experimental randomized complete blok design (DBCA) was used with 3 treatments and 3 repetitions. Variance analysis was performed, consecutively of a Duncan test for the separation of means, both analyzes with 0.05 significance. It was found that there is no significant difference between T1, T2 and T3 treatments for the number of leaves; for the other parameters if there is a significant difference being the best treatment T2 (puquio wáter) with a fresh weight of a lettuce of (291.08 g) followed by the T1 treatment with a fresh weight of (284.05 g) and finally the Treatment T3 with a fresh weinght of (251.3 g).